Social Grants Impact on Household Livelihoods: Empirical Evidence from International Migrants in Cape Town, South Africa - Jonas Nzabamwita; Emmanuel Ndhlovu (E-Journal of Humanities, Arts and Social Sciences)
South Africa has rolled out several social protection programmes targeted at various categories of people, including children, the elderly, the disabled, and the unemployed. Migrants also access social assistance as a livelihood mechanism. However, while existing studies link the country’s social protection initiatives with reductions in poverty, inequality, and unemployment, much of the data used to back these claims are drawn from quantitative surveys that rarely incorporate the livelihood plight of migrants. This has enormous policy and practical implications. This article seeks to close this gap by examining the role of social grants in migrants’ livelihoods in Cape Town, South Africa. Underpinned by exploratory and descriptive research designs, this mixed research methods study used primary data drawn from migrant household heads receiving social grants and key informants from migrant-serving organisations and focus group discussions. Descriptive and inferential statistics were used for quantitative data, while thematic data analysis was used for qualitative data. The results showed that besides the traditional short-term protective role of consumptive expenditure, social grants play a long-term promotive role in facilitating access to education and health and improving access to accommodation, water, and energy for migrants. To maximise social grants’ protective and promotive roles in migrant communities, this article recommends deploying proactive steps, including raising the value of grants, providing financial literacy training, and combining social grants with other programmes. The study adds to ongoing debates on the quality and effectiveness of social protection strategies in South Africa. It also flags policy directions for policymakers and other stakeholders working on social protection in South Africa.